Influence of steam in carbonation stage on CO2 capture by Ca-based industrial waste during calcium looping cycles. (23rd February 2016) - He, Zirui; Li, Yingjie; Ma, Xiaotong; Zhang, Wan; Chi, Changyun; Wang, Zeyan
Abstract: This work investigated the effect of steam concentration in carbonation on CO2 capture by carbide slag during the calcination/carbonation cycles in a dual-fixed bed reactor. Under severe calcination conditions, the pore structure of calcined carbide slag carbonated in the presence of 20 vol. % steam is better than that in the presence of 60 vol. % steam. In the presence of steam in carbonation, the drop of carbide slag in carbonation conversion under severe calcination conditions (950 °C, pure CO2 ) is relatively smaller than that without steam. Higher steam concentration results in significantly higher carbonation conversion of carbide slag for short carbonation duration (e.g., 5 min), because higher steam concentration leads to greater accelerating effect on CO2 diffusion through product layer. Steam exhibits a two-side effect on the carbonation performance of carbide slag, and the effect of high steam concentration on carbonation conversion is higher than that on pore structure. Highlights: Steam exhibits a two-side effect on the cyclic carbonation behavior of carbide slag. High steam concentration raises rapidly 5 min carbonation conversion of carbide slag. High steam concentration doesn't always boost 20 min conversion of carbide slag. Long carbonation in presence of steam has bad effect on CO2 capture by carbide slag. Effect of steam on carbonation of carbide slag is higher than that on pore structure.